A mechanistic study on the carrier properties of nitrogen-doped graphene derivatives using thermoelectric effect. (June 2017) - Tu, Nguyen Dien Kha; Lim, Jung Ah; Kim, Heesuk
Abstract: For graphene to find wide applicability in various nanoelectronic applications, it must be synthesized in bulk with reliable n - and p -type electrical properties. Most nitrogen-doped graphenes show p -type character despite their high nitrogen contents, leading to a lack of the n -type graphene. Here, we demonstrate that the reason why the pristine n -type graphene derivatives exhibit p -type character is due to unintentional hole doping by water and oxygen molecules from surroundings, which was firstly confirmed by understanding the electrochemical potential of graphene and water/oxygen layer. Furthermore, we show that this unintentionally p -doped graphene derivative can be changed to air-stable n -type by the surface charge transfer doping using polyethylenimine with the electron donating groups. The carrier properties of graphene derivatives were investigated using thermoelectric effects. These results demonstrate that the mechanistic and systematic study proposed here for controlling the carrier properties of graphene derivatives has great potential for further development of graphene-based electronic and energy devices. Graphical abstract: